European Community - Morris, Brian. author. aut Link
XXXVI, 348 p.
Keywords: An explanation of European Community law and bureaucracy in everyday terms. It explains how the Community itself works, with special diagrams and information on Community institutions, policy-making bodies, and private sector agencies with whom the Community consults.